1999
DOI: 10.1159/000026419
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Inhibits NMDA-Stimulated GnRH Secretion: Associated Effects on the Release of Hypothalamic Inhibitory Amino Acid Neurotransmitters

Abstract: Immune system activation is often accompanied by alterations in the reproductive axis. Interleukin-1 (IL-1), a polypeptide cytokine, has been postulated as a chemical messenger between the immune and the neuroendocrine systems. Using superfused hypothalamic fragments explanted from intact male rats, we evaluated the effects of IL-1 (0.5 and 5 nM) on basal and N-methyl-D-aspartate (NMDA)-stimulated release of gonadotropin-releasing hormone (GnRH), and the associated modifications in the output of inhibitory ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…IL-1 potentiates GABA signalling through multiple mechanisms: it recruits GABA A receptors to the cell surface76; it increases Cl − uptake by acting on GABA A receptors77; and it induces a delayed potentiation of the GABA-elicited Cl − current, an effect that is suppressed by the IL-1 receptor antagonist76. The observation that IL-1 potentiates the effects of GABA in the DRN is in agreement with data which demonstrate that IL-1 enhances GABA-induced hyperpolarization and inhibition in other brain regions where IL-1 acts both pre- and postsynaptically: IL-1 increases GABA release in anterior hypothalamic/pre-optic area slice preparations78 and in brain explants79 and enhances GABAergic inhibitory postsynaptic potentials in hippocampal neurons80,81.…”
Section: Interactions Between Il-1 and 5-htsupporting
confidence: 88%
“…IL-1 potentiates GABA signalling through multiple mechanisms: it recruits GABA A receptors to the cell surface76; it increases Cl − uptake by acting on GABA A receptors77; and it induces a delayed potentiation of the GABA-elicited Cl − current, an effect that is suppressed by the IL-1 receptor antagonist76. The observation that IL-1 potentiates the effects of GABA in the DRN is in agreement with data which demonstrate that IL-1 enhances GABA-induced hyperpolarization and inhibition in other brain regions where IL-1 acts both pre- and postsynaptically: IL-1 increases GABA release in anterior hypothalamic/pre-optic area slice preparations78 and in brain explants79 and enhances GABAergic inhibitory postsynaptic potentials in hippocampal neurons80,81.…”
Section: Interactions Between Il-1 and 5-htsupporting
confidence: 88%
“…Earlier studies demonstrated inhibitory eVects of IL-1 on the hippocampal long-term potentiation (LTP) [67]. The exact mechanisms of the inhibitory eVects of IL-1 on synaptic plasticity are not completely elucidated; however, in vitro studies performed on pharmacologically isolated NMDA receptors revealed that administration of IL-1 was associated with signiWcant decrease in NMDA receptor excitatory post-synaptic potentials [14,41]. Similar eVects with regard to LTP were observed in the transgenic mouse model over-expressing IL-6.…”
Section: Cytokines and Brain Plasticitymentioning
confidence: 99%
“…IL‐1 enhances GABA inhibitory effects acting at both pre‐ and post‐synaptic levels. IL‐1 enhances GABA release (Feleder et al ., 2000; Tabarean et al ., 2006) and it also enhances GABA‐induced post‐synaptic responses in different in vivo and in vitro experimental models (Miller et al ., 1991; Luk et al ., 1999; Serantes et al ., 2006). The present study was designed to test the hypothesis that IL‐1 inhibits DRN serotonergic neurons by potentiating GABAergic inhibition.…”
Section: Introductionmentioning
confidence: 99%